2017
DOI: 10.3389/fimmu.2017.00541
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Modulates the Response of Mast Cells to Staphylococcus aureus Infection

Abstract: To study the antimicrobial function of immune cells ex vivo, cells are commonly cultivated under atmospheric oxygen concentrations (20–21%; normoxia), although the physiological oxygen conditions in vivo are significantly lower in most tissues. Especially during an acute infection, oxygen concentration locally decreases to hypoxic levels around or below 1%. The goal of this study was to investigate the effect of hypoxia on the activity of mast cells (MCs). MCs were cultivated for 3 or 24 h at 1% O2 in a hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Accumulating data have indicated that HIF‐1a affects degranulation and the expression of inflammatory factors in MCs . A recent study demonstrated that HIF‐1a could contribute to the response to Staphylococcus aureus infection in MCs under hypoxia . In the present study, the HIF‐1a signaling pathway was also significantly modulated by DEPs in H5N1 virus‐infected HMCs.…”
Section: Discussionsupporting
confidence: 63%
“…Accumulating data have indicated that HIF‐1a affects degranulation and the expression of inflammatory factors in MCs . A recent study demonstrated that HIF‐1a could contribute to the response to Staphylococcus aureus infection in MCs under hypoxia . In the present study, the HIF‐1a signaling pathway was also significantly modulated by DEPs in H5N1 virus‐infected HMCs.…”
Section: Discussionsupporting
confidence: 63%
“…McGovern et al and Hoenderdos et al found that this hypoxia-augmented degranulation occurred rapidly (within 2 h), was not prevented by inhibition of protein translation, and could not be recapitulated by pharmacological HIF-1α stabilisation [24,32]. Together these data suggest that hypoxia drives an early increase in the release of pre-formed proteins and proteases in a manner that can be partially or totally HIF-independent, analogous to the increased release of histamine from mast cells [65] and WPBs from endothelial cells [75], but in contrast to IL-8 release from macrophages, which was HIF-independent but reliant on new protein synthesis [70]. Of interest, variable responses to different agonists have been seen in neutrophils, with both PAF and GM-CSF, but not TNF-α, able to promote hypoxic degranulation [24].…”
Section: Hypoxia Enhances Neutrophil Degranulationmentioning
confidence: 95%
“…Hypoxia has been shown to modulate protein secretion from several cell types, including immune cells and endothelial cells. Steiner et al showed that rats exposed to systemic hypoxia experienced a rapid (within minutes) and sustained increase in mast cell degranulation in vivo [64], and the hypoxic culture of mast cells demonstrated a HIF-independent increase in release of pre-stored histamine assessed at 3 h [65]. Conversely, TNF-α secretion was decreased, and transcriptomic analysis revealed the downregulation of Sec24A, which is implicated in cytokine transport from the endoplasmic reticulum to the Golgi.…”
Section: Effect Of Hypoxia On Protein Secretion From Non-neutrophilsmentioning
confidence: 99%
“…Mast cells also play an important protective role against various microbial infections, like S. aureus , by phagocytosis and by releasing mediators (e. g. tumor necrosis factor-α and histamine) [45]. However, it was proven that in the S. aureus -infected mice, severe infiltration of inflammatory cells in the dermis was observed, and mast cells were markedly accumulated in the skins.…”
Section: Skin Immune Systemmentioning
confidence: 99%